Meminimasi Waste Pada Proses Fabrikasi Struktur Baja dengan Konsep Lean Manufacturing Menggunakan Metode Value Stream Mapping (Studi Kasus PT. CDB) - Tina Hernawati Suryatman; Eli Cahya Aprilia (Universitas Muhammadiyah Tangerang, 2022)
PT. CDB is a company engaged in the field of General Contractor. In the fabrication process, there are various obstacles that hinder product delivery, resulting in project being delayed in erecting. The obstacles faced are the presence of activities or activities that are waste in the fabrication process, waste contained in the fabrication process, namely motion waste, waste waiting, and waste defects. This study aims to eliminate or streamline one of the processes in fabrication, identify waste that occurs during the fabrication process and propose improvements to minimize waste with the method used in this study, namely Value Stream Mapping and supported by several tools, namely Fishbone Diagram, Why-why Analysis and 5W+1H.found Waste and improvements can also be proposed to minimize waste. Suggestions for waste waiting, namely the merging of the fabrication process, waste defect by scheduling the welder and waste motion by reducing the forconstruction beginning so that manpower can do preparation. Based on the proposed improvements, a percentage comparison of the results of the lead time before and after repairs is generated. It can be seen that there is a time difference, there is a time difference resulting from the previous process, the fabrication process is faster or the time is reduced from 279 minutes to 225 minutes, there has been a reduction in time of 54 minutes or a reduction in waste of 19.42%.Keywords : General Contractor, Waste, Steel Structure Fabrication, Value Stream Mapping, Fishbone Diagram